ECOLOGICAL HOMEORHESIS IN THE MECHANISMS OF VIRULENCE EVOLUTION AND PENETRATION OF AGENTS OF FERAL HERD INFETIONS INTO HUMANS - A. V. Dubov (Детские инфекции (Москва))
We defined the characteristics of formation of ecological homeorhesis in feral herd infections (as exemplified by tick-borne encephalitis). By ecological homeorhesis we understand the process of harmonization between ecological factors and homeostasis systems on population, species and especially interspecies levels. We marked the evolution of epidemiology and clinical features of feral herd infections under anthropogenic influence upon natural hot spots. We also found in the circulation in endotherms and Lyme ticks the participation of such agents, which are unusual for these hot spots.